Outcome-oriented public management : a responsibility-based approach to the new public management - Schedler, Kuno; Proeller, Isabella (Research in public management (Unnumbered), 2010)
After the New Public Management had evolved in English speaking countries, it became a role model for the reform of public administration all throughout the world. Although there were obvious similarities in terminology used in different countries, the model was usually adapted to the cultural and political context in which it had to be embedded. This also resulted in significant conceptual differences, so that nowadays, there is no one single NPM in the world.In contrast to the original NPM model, this version puts emphasis on responsibility rather than accountability of public managers; it is strictly focused on the outcomes of public services rather than the output level; and it is grounded on the Rechtsstaat tradition of Continental European countries. Thus, the label that has been used in German ever since, Wirkungsorientierte Verwaltungsführung, is consequently translated into 'outcome-oriented public management' (OPM).This book is an English version of a German classic teaching book. In its original form, it was first published in 2000 and constantly revised according to latest developments in practice. Currently, it's 4th edition is selling in German speaking countries. Written for students and practitioners in public administration, the book describes the OPM model and its roots, and it discusses benefits and drawbacks of this model in practice. It is a perfect introduction into the new thinking of outcome orientation in the public sector.